Development of nanoemulsion-based hydrogel containing andrographolide: physical properties and stability evaluation - Oktavia Indrati; Ronny Martien; Abdul Rohman; Akhmad Kharis Nugroho (Wolters Kluwer Medknow Publications, 2020)
Introduction: Andrographolide is a compound that shows various pharmacological activities, which can be applied topically or orally. Nanoemulsion can improve drug solubility and stability, but has limitations for topical application. Incorporation of nanoemulsion into hydrogel can increase the viscosity of the system which can prolong the drug residence time. The aim of this study was to develop andrographolide nanoemulsion-based hydrogel for topical application. Method: Andrographolide nanoemulsion was prepared using Capryol 90 as the oil, Kolliphor RH 40 as the surfactant, and propylene glycol as the cosurfactant. Droplet size and polydispersity index of the nanoemulsions were evaluated using particle size analyzer. D-optimal mixture design was employed to generate the total number of runs (formulation), and obtain the optimum formulation. Fourteen formulations of nanoemulsion-based hydrogel were prepared by incorporating nanoemulsion into the hydrogel base (1:1). Carbopol was employed as the gelling agent, whereas other excipients including propylene glycol, oleic acid, triethanolamine, methylparaben, and propylparaben were also added to produce hydrogel base. Nanoemulsion-based hydrogel was evaluated for its pH, viscosity, and physical appearance (after 8 weeks of storage). Results: The result revealed that nanoemulsion-based hydrogel containing 34.65% of carbopol, 1.35% of triethanolamine, and 9% of propylene glycol was selected as an optimum formulation which shows acceptable pH, viscosity, and physical appearance. This optimum nanoemulsion-based hydrogel has pH of 6.50 ± 0.02, and 2492.33 ± 36.91 cP of viscosity with milky white color, and smooth homogeneous texture. Conclusion: This study suggested that andrographolide can be successfully formulated into an acceptable nanoemulsion-based hydrogel.